PEPTIC ULCER DISEASE - Archampong, E.Q. (My University, 2013)
Nothing short of a revolution has transpired in our understanding of the aetiology, pathogenesis and the management of peptic ulcer disease over the past century, and the burning issue is how far this has influenced the outcome of management. Dominance of treatment by surgical intervention based on the acid dogma “no-acid, no ulcer” has given way to conservative measures aimed at elimination of helicobactor pylori using short term antibiotic regimes. This chapter represents a descriptive study through review of the literature on the outcome of these interventions over the past half century. The study is supplemented with the outcome of interviews with colleagues on their practice as physicians and surgeons in the Korle-Bu Teaching Hospital. It is evident that in the local practice as elsewhere the management of peptic ulcer disease has become increasingly conservative; surgical interventions are virtually confined to complications – perforations, bleeding and cicatrisation. Control of the disease within the communities has been effective, but for problems of compliance on account of access to the necessary drugs in the community.